2015
DOI: 10.1016/j.jval.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid Versus Vancomycin in the Empiric Treatment of Nosocomial Pneumonia: A Cost-Utility Analysis Incorporating Results from the ZEPHyR Trial

Abstract: Linezolid may be a cost-effective alternative to vancomycin in the empiric treatment of patients with suspected MRSA nosocomial pneumonia; however, results of our model were highly variable on a number of important variables and assumptions including mortality differences and time frame analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
2
17
0
1
Order By: Relevance
“…HAP caused an increase of $11,897 to $25,072 per incident and was the leading cause of death in all nosocomial infections [49]. In four pharmacoeconomic analyses comparing vancomycin and linezolid in the treatment of pneumonia, efficacy and cost data were obtained from published RCTs [5053]. Our results confirmed the results of previous analyses and showed that despite its higher cost, linezolid was cost-effective for treatment of MRSA pneumonia.…”
Section: Discussionsupporting
confidence: 83%
“…HAP caused an increase of $11,897 to $25,072 per incident and was the leading cause of death in all nosocomial infections [49]. In four pharmacoeconomic analyses comparing vancomycin and linezolid in the treatment of pneumonia, efficacy and cost data were obtained from published RCTs [5053]. Our results confirmed the results of previous analyses and showed that despite its higher cost, linezolid was cost-effective for treatment of MRSA pneumonia.…”
Section: Discussionsupporting
confidence: 83%
“…In a Chinese perspective, linezolid was more cost-effective than vancomycin, considering adverse effects of this drug 23 . Other studies from different points of view showed similar results with our study 24,25 . The theorical burden of vancomycin related renal failure is questionable in cost-analysis publications 26 .…”
Section: Discussionsupporting
confidence: 92%
“…Some studies demonstrated that administration of linezolid is more cost-effective than vancomycin in the treatment of MRSA infection because of earlier discharge from the hospital. 66 , 67 Generally, linezolid may reduce mortality of patients compared to vancomycin. 68 , 69 …”
Section: Comparison With Other Antibioticsmentioning
confidence: 99%